Temozolomide Treatment Induces HMGB1 to Promote the Formation of Glioma Stem Cells via the TLR2/NEAT1/Wnt Pathway in Glioblastoma - Gao, Xiang-Yu; Zang, Jian; Zheng, Min-Hua; Zhang, Yu-Fei; Yue, Kang-Yi; Cao, Xiu-Li; Cao, Yuan; Li, Xin-Xin; Han, Hua; Jiang, Xiao-Fan; Liang, Liang (Frontiers in Cell and Developmental Biology, 2021)
Formation of glioma stem cells (GSCs) is considered as one of the main reasons of temozolomide (TMZ) resistance in glioma patients. Recent studies have shown that tumor microenvironment-derived signals could promote GSCs formation. But the critical molecule and underlying mechanism for GSCs formation after TMZ treatment is not entirely identified. Our study showed that TMZ treatment promoted GSCs formation by glioma cells; TMZ treatment of biopsy-derived glioblastoma multiforme cells upregulated HMGB1; HMGB1 altered gene expression profile of glioma cells with respect to mRNA, lncRNA and miRNA. Furthermore, our results showed that TMZ-induced HMGB1 increased the formation of GSCs and when HMGB1 was downregulated, TMZ-mediated GSCs formation was attenuated. Finally, we showed that the effect of HMGB1 on glioma cells was mediated by TLR2, which activated Wnt/β-catenin signaling to promote GSCs. Mechanistically, we found that HMGB1 upregulated NEAT1, which was responsible for Wnt/β-catenin activation. In conclusion, TMZ treatment upregulates HMGB1, which promotes the formation of GSCs via the TLR2/NEAT1/Wnt pathway. Blocking HMGB1-mediated GSCs formation could serve as a potential therapeutic target for preventing TMZ resistance in GBM patients.